If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4y+4=-6y-8
We move all terms to the left:
-4y+4-(-6y-8)=0
We get rid of parentheses
-4y+6y+8+4=0
We add all the numbers together, and all the variables
2y+12=0
We move all terms containing y to the left, all other terms to the right
2y=-12
y=-12/2
y=-6
| n+4/2+3=13 | | 13.81+39.28x=92.37 | | 9x+210=4x+110 | | 12+3x=99 | | -8=4(y-3)-8y | | -37=5w-8 | | .375+50+x=31=180 | | 2(r+10)=240 | | 1-x+4+17x=-3x | | 7x-10+6x+9=180 | | 4-9x=-16 | | -1=-6+5w | | -10j=-9j-6 | | y=6+1/2 | | 5+3p-p=8=3(p+2) | | (5c)(5)= | | 7+w/2=1 | | 115=3(1+5b)-b | | -7-7h=-8h | | (3x+20)+(3x+20)=180 | | -29=5c+6 | | -7−7h=-8h | | -7+8z=7z | | 4+x-3=96 | | 3(x=5)=30÷5 | | (5x-3)=32 | | v/4=52 | | (3/4x-13)+(3x-17)=90 | | 3x+15+5x-3=180 | | 0.25n=5.25 | | -6w=6-7w | | 3n-25=32 |